1990
DOI: 10.1093/jpepsy/15.6.711
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Depression in Mothers of Failure-to-Thrive Children

Abstract: Compared 30 mothers whose children were hospitalized for failure-to-thrive (FTT) to a normative group on standardized measures of perceived stress and depression. Child and maternal medical and demographic data were also taken. Standardized development and feeding assessments were done. Descriptive statistics, correlational analyses, and t tests were used to describe and examine group differences. FTT children were perceived overall as more stressful, less adaptable, more inconsolable, and more unhappy than we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 12 publications
1
40
0
2
Order By: Relevance
“…Previous research has shown that mothers of children with feeding problems often have higher levels of depression and anxiety (Blissett et al, 2007;Chatoor, Hirsch, Ganiban, Persinger, & Hamburger, 1998;Coulthard & Harris, 2003;Duniz et al, 1996;Lindberg, Bohlin, Hagekull, & Palmerus, 1996;Whelan & Cooper, 2000), emotional distress (Budd et al, 1992), parenting stress (Singer, Song, Hill, & Jaffe, 1990;Spender et al, 1996) and poorer problem-solving abilities (Ünlü, Aras, Guvenir, Buyukgebiz, & Bekem, 2006). Farrow and Blissett (2006b) also reported that in a group of ninety-nine mothers the most common factor associated with feeding difficulties was low self-esteem and feelings of social isolation.…”
Section: Emotional Support As a Vehicle For Interventionmentioning
confidence: 99%
“…Previous research has shown that mothers of children with feeding problems often have higher levels of depression and anxiety (Blissett et al, 2007;Chatoor, Hirsch, Ganiban, Persinger, & Hamburger, 1998;Coulthard & Harris, 2003;Duniz et al, 1996;Lindberg, Bohlin, Hagekull, & Palmerus, 1996;Whelan & Cooper, 2000), emotional distress (Budd et al, 1992), parenting stress (Singer, Song, Hill, & Jaffe, 1990;Spender et al, 1996) and poorer problem-solving abilities (Ünlü, Aras, Guvenir, Buyukgebiz, & Bekem, 2006). Farrow and Blissett (2006b) also reported that in a group of ninety-nine mothers the most common factor associated with feeding difficulties was low self-esteem and feelings of social isolation.…”
Section: Emotional Support As a Vehicle For Interventionmentioning
confidence: 99%
“…Davies and colleagues hold that the current classification system fails to encompass the full range of feeding difficulties and places undue emphasis on the problem being solely the child's, failing to capture important contexts in which the child lives. 22 Although child factors such as temperament [23][24][25] ; organic conditions 26 ; structural abnormalities or dysphagia [27][28][29] ; and developmental problems and syndromes [30][31][32] have been linked with the pathogenesis of FDs, environment and parental factors may also interact to influence and maintain the problems. 18 Research that has focused on maternal/caregiver influences has found mothers of children with FD to (a) be more unpredictable, coercive, controlling, insensitive, intrusive, and over-stimulating, (b) be less flexible, accepting, and affectionate, (c) be more likely to use physical punishment or forcefeeding, (d) have difficulty receiving the child's signals, and (e) show more anger and hostility during interaction with their children.…”
Section: Feeding Disorder Of Infancy or Early Childhoodmentioning
confidence: 99%
“…Persistent inadequate intake or substantially unbalanced diets can result in weight loss, malnutrition, lethargy, and even impaired mental or physical development (Christopherson & Hall, 1978). Furthermore, families of children with feeding problems are at high risk for stress and mental health issues (Singer, Song, Hill, & Jaffe, 1990). Thus, the successful treatment of feeding problems has a number of important implications, such as improved health in children, improved quality of life for children and families, decreased mental health problems in families, and reduced risk of long-term eating problems (Piazza & Carroll-Hernandez, 2004).…”
mentioning
confidence: 99%